121 High Risk Subset of Grade 1 Endometrioid Endometrial Adenocarcinomas Associated With Aggressive Behavior. (11th January 2018) - Sanchez, Daniel
Abstract: Background: Conventional low-grade endometrioid endometrial adenocarcinomas have been associated with lower risk of cervical and adnexal involvement and extrauterine spread, and therefore lower stage at diagnosis. Most type 1, grade 1 endometrioid adenocarcinomas are PTEN deleted, express estrogen and progesterone receptors, and are p53 intact, which portends a better prognosis. Methodology: In our retrospective analysis, we examined 220 cases of type 1, grade 1 endometrioid endometrial adenocarcinomas (n = 220). Each case was reviewed with the pertinent H&E and immunohistochemistry, and the evaluated parameters included age of the patient, size of tumor, percent of myometrial involvement, angiolymphatic invasion, cervical involvement, expression of ER, PR, p53, PTEN, and MSI, lymph node involvement, and pathologic stage. Results: Out of the 200 cases, 186 shared the conventional immunophenotype, and 34 shared a variant immunophenotype characterized by loss of progesterone (23 cases, 67.6%), p53 mutation (16 cases, 47.1%), or PTEN wild type (five cases, 14.7%). The 34 variant cases of type 1, grade 1 endometrioid endometrial adenocarcinoma were associated with cervical involvement, extrauterine spread (eight cases, 23.5%, P = .031) and lymph node metastasis. Conclusion: There is a subset "variant" of grade 1 endometrioid endometrial adenocarcinomas that expresses a different immunophenotype compared to the conventional type. These variant grade 1 endometrioid adenocarcinomas that have loss of progesterone, p53 mutated, PTEN wild type are associated with a high-risk biology and portend a more aggressive clinical course when compared to the conventional grade 1 endometrioid adenocarcinoma. The aggressive nature of the variant grade 1 endometrioid adenocarcinoma is independent of percent of myometrial invasion. Based on these findings, it is recommended to treat these variants of grade 1 endometrioid endometrial adenocarcinomas similar to grade 3 endometrioid adenocarcinoma and due to their aggressive biology and risks of extrauterine spread, lymph node involvement, and higher stage at diagnosis to perform pelvic lymphadenectomy and stage them similar to the high grades. Management should not depend on percent of myometrial involvement due to the present finding of extrauterine disease in cases with less than 50% of myometrial involvement.